2004
DOI: 10.1002/pssc.200304396
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Bi mole ratio on phase formation in Bi x Y 3− x Fe 5 O 12 nanoparticles

Abstract: A series of Bi substituted yttrium iron garnet (Bi-YIG) nanoparticles with nominal formula of Bi x Y 3-x Fe 5 O 12 , in which x varied in the steps of 0.0, 0.5, 1.0 and 1.5, were prepared via mechanochemical processing (MCP). A milling time of 5 hours was found to be suitable for all the samples. Minimum annealing temperature for completion of the phase formation was determined for each sample. The optimum annealing temperature of each sample is much lower than the annealing temperature for the completion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…One can observe that the crystallization process of the YIG precursor begins at 300 • C, and the Fe 2 O 3 crystal is the preferred formation at this stage. Consequently, the YIG crystal is formed when the calcination temperature is over 600 • C. Notably, this calcination temperature of YIG is obviously lower than that reported in the literature [4,5]. However, Fig.…”
Section: Characteristics Of Yig Precursorcontrasting
confidence: 53%
See 1 more Smart Citation
“…One can observe that the crystallization process of the YIG precursor begins at 300 • C, and the Fe 2 O 3 crystal is the preferred formation at this stage. Consequently, the YIG crystal is formed when the calcination temperature is over 600 • C. Notably, this calcination temperature of YIG is obviously lower than that reported in the literature [4,5]. However, Fig.…”
Section: Characteristics Of Yig Precursorcontrasting
confidence: 53%
“…Among them, ball milling of Y 2 O 3 and Fe 2 O 3 powders [4] at high temperature is usually used to synthesize YIG [5]. However, this method needs a high sintering temperature (>1300 • C), and thus it is hardly used in multilayer microwave components because the melting points of highly conductive metals such as Ag-Pd alloy are lower than that of YIG.…”
Section: Introductionmentioning
confidence: 98%
“…Various techniques have been used to prepare well crystalline YIG nanopowders including co-precipitation [6][7][8], sol-gel [1,9,10], microemulsion [12], organic precursor method [13][14][15], hydrothermal [16] and mechanochemical [17] techniques. It has been demonstrated that the chemical co-precipitation method is the most suitable technique due to its low-cost in addition to its suitability for the mass production.…”
Section: Introductionmentioning
confidence: 99%
“…This is in view the fact that by increasing Bi 3+ , the densities of samples will increase. This is because the effect of Bi 3+ atomic weight on density of Bi-substituted garnets is more dominant than its effect of the ionic radius [6]. It can be seen with increase x value coercivity drastically reduced.…”
Section: Resultsmentioning
confidence: 96%